KONTRIBUSI SISTEM INFORMASI MANAJEMEN DALAM MENINGKATKAN MUTU PENDIDIKAN - Lutfi, Ahmad Syamsu; Chotimah, Chusnul; Junaris, Imam (Program Studi Manajemen Pendidikan Islam, 2023)
The management information system is a set of information systems that provide output using an input as well as various processes needed to achieve the objectives contained in an educational management process. With the existence of a management information system, the preparation of information can be easily arranged properly so that it is in accordance with the wishes of the customer. In addition, the contribution of management information systems can assist in presenting precise and accurate data as well as fast and flexible. For this reason, it can be understood that the information management system has a very large contribution to improving the quality of education. This study aims to analyze and determine the contribution of management information systems in improving the quality of education. This study uses the method of library analysis by utilizing library resources to obtain theories and limiting activities only to library collection materials and other factual references.